Demographic Factors Associated With Successful Telehealth Visits in Inflammatory Bowel Disease Patients. Issue 3 (26th March 2021) - Shah, Kaustav P; Triana, Austin J; Gusdorf, Roman E; McCoy, Allison B; Pabla, Baldeep; Scoville, Elizabeth; Dalal, Robin; Beaulieu, Dawn B; Schwartz, David A; Griffith, Michelle L; Horst, Sara N
Abstract: Background: This study evaluated synchronous audiovisual telehealth and audio-only visits for patients with inflammatory bowel disease (IBD) to determine frequency of successful telehealth visits and determine what factors increase the likelihood of completion. Methods: Data were collected from March to July 2020 in a tertiary care adult IBD clinic that was transitioned to a fully telehealth model. A protocol for telehealth was implemented. A retrospective analysis was performed using electronic medical record (EMR) data. All patients were scheduled for video telehealth. If this failed, providers attempted to conduct the visit as audio only. Results: Between March and July 2020, 2571 telehealth visits were scheduled for adult patients with IBD. Of these, 2498 (99%) were successfully completed by video or phone. Sixty percent were female, and the median age was 41 years. Eighty six percent of the population was white, 8% black, 2% other, and 4% were missing. Seventy-five percent had commercial insurance, 15% had Medicare, 5% had Medicaid, and 5% had other insurance. No significant factors were found for an attempted but completely failed visit. Using a multivariate logistic regression model, increasing age (odds ratio, 1.80; 95% CI, 1.55–2.08; P < 0.05), noncommercial insurance status (odds ratio, 1.89; 95% CI, 1.61–2.21; P < 0.05), and black race (odds ratio, 2.07; 95% CI, 1.38–3.08; P < 0.05) increased the likelihood of a video encounter failure. Conclusions: There is a high success rate for telehealth within an IBD population with defined clinic protocols. Certain patient characteristics such as age, race, and health insurance type increase the risk of failure of a video visit.